An analysis of fog computing data placement algorithms - Silva, D. M. A. da.; Asaamoning, G.; Orrillo, H.; Sofia, R. C.; Mendes, P. M. (MobiQuitous '19: Proceedings of the 16th EAI International Conference on Mobile and Ubiquitous Systems: Computing, Networking and Services, 2019)
This work evaluates three Fog Computing data placement algorithms via experiments carried out with the iFogSim simulator. The paper describes the three algorithms (Cloud-only, Mapping, Edge-ward) in the context of an Internet of Things scenario, which has been based on an e-Health system with variations in applications and network topology. Results achieved show that edge placement strategies are beneficial to assist cloud computing in lowering latency and cloud energy expenditure.